Legal Grounds and Prospects for Public Participation in Climate Protection Projects - Polish Experience - Haładyj, Anna (Polish Yearbook of Environmental Law, 2014)
The aim of this study is to answer the question which legal instruments enable the Poles to involve in issues concerning development (and later implementation) of the public policy on the climate change. Taking into account the mistrust towards the governmental authorities, as well as the underdevelopment of the Polish civic society, I assume that the level of the public participation in climate protection projects is low. The blame for this state of affairs is also to be put on the weakness of the legal instruments for the public participation in climate protection.